Men at Work, Fathers at Home: Uncovering the Masculine Face of Caregiver Discrimination - Cunningham-Parmeter, Keith (Columbia Journal of Gender and Law, 2013)
Despite their many workplace advances, women remain constrained by an enduring social expectation that they will manage their families’ domestic lives. Women will not achieve full workplace equality until men do more at home, and men will not enter the domestic sphere if they face employment retaliation for doing so. Men at Work, Fathers at Home addresses this problem by critically evaluating the legal challenges that fathers and other male caregivers face in proving claims of workplace discrimination. Drawing from Supreme Court precedent and gender theory, the Article explains how masculine norms deter men from asserting their caregiving needs at work, while undermining their ability to prosecute discrimination claims in court. By examining how these men can combat biases against male caregiving, the Article seeks to advance the goal of gender equality for both sexes.